ANALISIS KEYAKINAN PENGAJAR BIPA PADA EFEKTIVITAS PROGRAM VISITING LECTURER BAGI PEMBELAJAR MEDAGASKAR - Kurniawati, Rikke; Laksono, Kisyani; Nurhadi, Didik (Jurnal Muassis Pendidikan Dasar, 2024)
Teacher beliefs basically greatly contribute to the response and meaning given to students regarding learning objects or events. Meanwhile, effectiveness is an analysis to measure or determine the level of effectiveness of ongoing learning. This research aims to analyze the level of confidence of BIPA teachers in the visiting lecturer program. This research uses a mixed method with a sequential explanatory design model. The subjects of this research were 30 BIPA teachers at the Language Tower and Language Train Institutes. Data collection was carried out by distributing instruments and conducting interviews with BIPA teachers and users at the Language Tower Institute and Language Train. Quantitative data was obtained by carrying out calculations with data obtained from existing incidental sampling and filling out instruments in the form of questionnaires distributed via Google Form. Data analysis was carried out quantitatively and qualitatively, where quantitative used averages and qualitative data analysis used descriptive. The research results show that the effectiveness of implementation on teachers' beliefs using the visiting lecturer program can be said to be very effective with data obtained from 37 users of the visiting lecturer program. Based on the results of the data analysis that has been obtained, it can be stated that the 14 BIPA teachers respondents at the Language Tower and Language Train Institute are confident that the visiting lecturer program is very effective in teaching Indonesian to facilitate the language acceptance process for Medagascar students.